Policies supporting for agricultural cooperatives in Vietnam: An experience from agricultural cooperatives in the Red River Delta - Nguyen Thi, Hai Ninh (Technium Social Sciences Journal, 2021)
Agricultural cooperatives have been established in Vietnam since the 1950s. During its development, agricultural cooperatives have made significant contributions to the growth of agricultural sector and to the improvement of farmers’ income who are members of the cooperatives. Since Vietnam implemented the "Innovation-Doi moi" in 1986, the Government has continued to issue many policies to support for agricultural cooperatives. However, the impact of these policies on the development of almost all agricultural cooperatives has not been as expected. This paper aims to analyze the implementation of several policies supporting for agricultural cooperatives; to identify advantages and disadvantages of these policies; and to propose solutions for improving policies in the furture. In addition to secondary data from the Vietnam Cooperative Alliance, this paper uses primary data collected from 60 agricultural cooperatives in the Red River Delta to analyze the implementation of policies on cooperative staffs training, cooperative finance supporting, and cooperative land supporting. Bascially, the results show that the policy on training cooperative staff is quite well implemented, it helps to improve the capacity of cooperative managers in all surveyed cooperatives. In contrast, the finance supporting policy has many regulations that make it difficult for agricultural cooperatives to access capital, only nearly 30% of surveyed cooperatives get loans for production. Similarly, the land supporting policy also has unreasonable regulations which prevent agricultural cooperatives from scaling-up production because of the lack of farm-land. Consequently, about 60% of surveyed cooperatives are supported to rent farm-land for expanding agricultural production.